Lactase deficiency and gastrointestinal allergies in young children - N. V. Ziatdinova; T. G. Malanicheva; L. A. Bareeva (Медицинский совет, 2020)
Intestinal colic, food allergies are one of the common causes of the initial treatment of children in their first year of life in outpatient practice. Gastrointestinal allergy is a lesion of the gastrointestinal tract of an allergic nature, is in second place among the pathologies associated with food allergies, where allergy to cow’s milk proteins leads. In recent years, the diagnosis of lactase deficiency, unreasonably leads to an unreasonable transfer of the child to artificial curing and the appointment of lactose-free mixtures. In some patients with gastrointestinal manifestations, secondary LN is quite often formed. The article discusses the clinical forms of LN and GA. Undigested lactose increases the cell-mediated pro-inflammatory processes in the body, which, in turn, leads to the stimulation of the development of inflammatory and allergic processes in children. The possibilities and effectiveness of concomitant diet therapy are discussed, including using replacement therapy with the enzyme lactase, which eliminates the main cause of childhood colic, helps the absorption of breast milk or mixture, thus providing babies with the necessary nutrients for physiological development. The article presents results of the clinical observation carried out in a group of 20 full term babies aged 2–5 months with secondary lactase deficiency in the setting of gastrointestinal allergy with positive clinical response: highly quick control of symptoms of intestinal dyspepsia, improvement in stool frequency and consistency were detected on Day 7 from the start of enzyme therapy in 85% of children. Symptoms of intestinal colic (95%), flatulence (80%) were also reversed, regurgitation decreased in frequency and volume (85%) by the end of Week 1 of the therapy and completely disappeared by the end of Week 2. Lab tests confirmed the clinical efficacy of the therapy. A significant improvement in coprogram indicators was identified in 80% of children by the end of Week 2 from the start of therapy. The researchers found out that the carbohydrate content in the coprogram decreased by 1.8 times from 1.3% ± 0.5 to 0.7% ± 0.5 (p <0.05) in most children, and there was no significant decrease of this indicator in 20% of patients. The results show that the prescription of enzyme replacement therapy in combined gastrointestinal allergy and secondary lactase deficiency in children aged 6 months helped keep breastfeeding volumes, and reverse symptoms of lactase deficiency in most cases.